Abiding in the Love of Jesus Creates Friendship Historical Chriticism of John 15:9-17 - Simon Petrus Lumbantoruan; Debora Sitohang; Ketler Sitohang; Binsar Simanjuntak; Dapot Damanik (International Journal of Christian Education and Philosophical Inquiry, 2024)
In everyday conversation the word “criticism” usually has an unfavorable or negative meaning. This word is often associated with a negative or bad assessment of something. But this can also have a positive impact. For example, art, literature, music, etc. In this case, criticism is a type of interpretation that seeks to systematically emphasize the properties of something. When applied to the Bible, this approach is often understood as a passive effort. However, this textual critical approach is a systematic effort to understand the Bible by examining its form, content, and context, studying it, explaining it, and exploiting the benefits of understanding it from everyone’s point of view. Regarding the Gospel of John, there are several things you need to know about his theology. Jesus had several titles that need to be looked at and studied to know their true meaning. The author uses qualitative methods to examine the history in which Jesus faced the Jews and the Roman empire. As well as the teachings that Jesus gave to His disciples.